May You Be Shot with Greasy Bullets: Curse Utterances in Turkish - Vancı Osam, Ülker (Nanzan University, 1998)
Curse utterances are a remarkable linguistic form. While some languages have few curse utterances, other languages, such as Turkish, are well known for their imaginative and numerous curse expressions. This study surveys the characteristics and functions of curse utterances in Turkish by examining specific examples with concepts from speech act theory and ethnography of communication. Throughout the study the examples will help to demonstrate that curse utterances are more than linguistic routines, as they allow their "addressors" to enjoy a high degree of creativity and verbal flexibility within rather strict morphological and syntactical rules.
The file in this item is the publisher version (published version) of the article.
Keywords: curse utterances; speech act theory; ethnography of communication